2009
DOI: 10.1007/s10530-009-9430-7
|View full text |Cite
|
Sign up to set email alerts
|

Melilotus officinalis (yellow sweetclover) causes large changes in community and ecosystem processes in both the presence and absence of a cover crop

Abstract: Non-native species are hypothesized to decrease native species establishment and cover crops are hypothesized to decrease non-native species abundance. Although many studies have compared invaded to non-invaded habitats, relatively few studies have experimentally added non-native species to directly examine their effects. In a greenhouse mesocosm experiment, we tested the effects of non-native forbs (Melilotus officinalis, Verbascum thapsus, and Lespedeza cuneata), a proposed C3 grass cover crop (Pascopyrum sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 45 publications
3
7
0
Order By: Relevance
“…Overall, the percentage of C 4 species was much higher in spring timing plots when the prairie mix was added simultaneously compared to all other treatments. Our results are consistent with Dickson et al (2010), who found that an exotic legume was able to out-compete native perennial C 4 prairie grasses because it established earlier. If exotic species green up earlier, have stronger priority effects and have higher aboveground growth rates than natives (Leishman et al 2007;Wilsey, Daneshgar & Polley 2011;Dickson, Hopwood & Wilsey 2012), then exotics may have large and underappreciated consequences for predicting community assembly history outcomes (Wolkovich & Cleland 2011). Variation in abiotic conditions between spring and summer timing treatments suggests that early invaders can modify their environments and contribute to community divergence.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Overall, the percentage of C 4 species was much higher in spring timing plots when the prairie mix was added simultaneously compared to all other treatments. Our results are consistent with Dickson et al (2010), who found that an exotic legume was able to out-compete native perennial C 4 prairie grasses because it established earlier. If exotic species green up earlier, have stronger priority effects and have higher aboveground growth rates than natives (Leishman et al 2007;Wilsey, Daneshgar & Polley 2011;Dickson, Hopwood & Wilsey 2012), then exotics may have large and underappreciated consequences for predicting community assembly history outcomes (Wolkovich & Cleland 2011). Variation in abiotic conditions between spring and summer timing treatments suggests that early invaders can modify their environments and contribute to community divergence.…”
Section: Discussionsupporting
confidence: 93%
“…Above-ground productivity was higher in the more diverse plots containing a greater proportion of native species that resulted from the assembly history treatments. Our results support the few existing studies (Foster & Dickson 2004;Ko¨rner et al 2008;Fukami et al 2010;Dickson et al 2010) that found that community assembly history has ecosystem-level ramifications.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…We observed that species diversity was greater in nativedominated than exotic-dominated fields in central Texas, a trend similar to that reported elsewhere for invasions by Agropyron cristatum (Christian and Wilson, 1999), Imperata cylindrica (Brewer, 2008), 13 invasive species in Europe (Hejda et al, 2009), Melilotus officionale (Dickson et al, 2010) and exotic C 3 grasses (Miles and Knops, 2010). Our observational data provide some support for the passenger model in that exotic species did not invade and drive down species diversity at all sites.…”
Section: Discussionsupporting
confidence: 89%